Numerical methods for nonlinear systems of equations - Wong, Ee Chyn (2014)
It is common to have nonlinear systems of equations to be solved in numerical application. However, such nonlinear systems of equations are difficult to be solved either exactly or numerically. There are several methods that can be used to solve the nonlinear systems of equations numerically such as Newton's method, quasi-Newton method, and homotopy continuation method. Some numerical examples of nonlinear systems of equations are shown in this study. Further, a heat transfer process is model as a problem that nonlinear system of equations is solved with the methods that had been mentioned earlier. The numerical results are computed by using MATLAB codes and the results are compared in order to determine the accuracy of these three methods.